Membangun Business Model: Sebuah Telaah Konseptual dan Pengalaman Praktis - Achmad Sobirin (Universitas Islam Indonesia, 2007)
Business model is relatively a new term that emerged in 1990s together with the mushroom of e-business. Conceptually business model is therefore still in infancy. Despite this fact however it does matter (Magretta, 2002). Business model which is conceived as the logic of doing business, a construct, a mental model or a business paradigm, is considered a guide on how to do every day’s business. Based on the above mentioned understanding, this paper based on action research study, discusses the implemention of the concept of business model on change management using the case of Universitas Islam swasta. The result indicates that changing business model will inevitably change the organizational architecture and governance.Keywords: business model, organizational architecture and governance.